2018
DOI: 10.1111/jhn.12609
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a Mediterranean diet supplemented with fatty fish in ameliorating inflammation in paediatric asthma: a randomised controlled trial

Abstract: How to cite this article Papamichael M.M., Katsardis Ch., Lambert K., Tsoukalas D., Koutsilieris M., Erbas B., Itsiopoulos C. (2019) Efficacy of a Mediterranean diet supplemented with fatty fish in ameliorating inflammation in paediatric asthma: a randomised controlled trial. J Hum Nutr Diet. 32,[185][186][187][188][189][190][191][192][193][194][195][196][197] .https://doi. AbstractBackground: Childhood asthma is the most common respiratory disorder worldwide, being associated with increased morbidity and a de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 52 publications
2
35
0
Order By: Relevance
“…Subjects with a higher O3I had a significantly lower range of maintenance ICS dose. A similar finding has been shown in a recent RCT by Papamichael et al [41], where children with asthma were prescribed a Mediterranean diet supplemented with two meals of 150 g cooked fatty fish per week for 6 months, compared to a control group following their normal diet. They found that while there was no difference between lung function, asthma control and quality of life scores, there was a significant reduction in medication use for children in the intervention group [41].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Subjects with a higher O3I had a significantly lower range of maintenance ICS dose. A similar finding has been shown in a recent RCT by Papamichael et al [41], where children with asthma were prescribed a Mediterranean diet supplemented with two meals of 150 g cooked fatty fish per week for 6 months, compared to a control group following their normal diet. They found that while there was no difference between lung function, asthma control and quality of life scores, there was a significant reduction in medication use for children in the intervention group [41].…”
Section: Discussionsupporting
confidence: 85%
“…A similar finding has been shown in a recent RCT by Papamichael et al [41], where children with asthma were prescribed a Mediterranean diet supplemented with two meals of 150 g cooked fatty fish per week for 6 months, compared to a control group following their normal diet. They found that while there was no difference between lung function, asthma control and quality of life scores, there was a significant reduction in medication use for children in the intervention group [41]. In a study examining exercise-induced bronchoconstriction, n-3 PUFA supplementation (3200 mg EPA + 200 mg DHA for eight weeks) has also been demonstrated to reduce bronchodilator use in adults [42].…”
Section: Discussionsupporting
confidence: 85%
“…Traditional Mediterranean diet is the dietary pattern that has been linked to a number of metabolic and health benefits, including reduced mortality risk and lower incidence of cardiovascular disease[6, 7] and reducing airway inflammation in asthma[8]. The benefits of even short periods of adherence to Mediterranean diet on inflammatory markers have been shown[9] and the adipose tissue inflammatory response, measured by IL-6, MCP-1, leptin and adiponectin gene expression[10], can be modulated by a single meal.…”
Section: Introductionmentioning
confidence: 99%
“…However, a recent Randomized Control Trial, a supplementation of 150 g cooked fatty fish in two meals per week, showed a significant reduction of bronchial inflammation after a 6-month intervention. FeNO values reduced on 14.15 ppb in comparison to those that were not supplemented [40].…”
Section: Discussionmentioning
confidence: 85%